Cinobufagin restrains the growth and triggers DNA damage of human hepatocellular carcinoma cells via proteasome-dependent degradation of thymidylate synthase. (1st June 2022) - Yang, Ailin; Wu, Qi; Chen, Qimei; Yang, Jingyi; Li, Haoran; Tao, Yufan; Wang, Anmei; Sun, Yaxue; Zhang, Jiayu
Abstract: Anti-tumor candidate drugs from natural products have gained increasing attention. Cinobufagin is a natural product isolated from the traditional chinese medicine Chansu. Herein, we find that cinobufagin inhibits the proliferation and colony-forming ability of human hepatoma HepG2 and SK-HEP-1 cells. Furthermore, cinobufagin induces G2-phase cell cycle arrest and DNA damage in cancer cells. Thymidylate synthase (TYMS), the major target of chemotherapeutic drugs 5-FU or other fluoropyrimidines, which catalyzes the conversion of dUMP to dTMP and provides the sole de novo source of thymidylate for DNA synthesis. We demonstrate that cinobufagin suppresses TYMS expression via proteasome-dependent degradation in human hepatoma cells, moreover, depletion of TYMS restrains the proliferation and colony formation of tumor cells, and the results of western blotting and immunofluorescence assay indicate DNA damage is induced in tumor cells transfected with TYMS-targeting siRNA (siTYMS), additionally, knockdown of TYMS enhances the inhibitory eﬀect of cinobufagin on the proliferative potential of HepG2 and SK-HEP-1 cells. It is worth noting that cinobufagin in combination with 5-FU exhibits antagonism or synergism combined effects on the proliferation of human hepatoma cells, indicating that Chansu-related preparations such as cinobufacini injection and Huachansu capsules applied to clinical practice should be used with caution in combination with 5-FU for the treatment of liver cancer. Collectively, cinobufagin exerts good anti-hepatoma activity through inhibition of growth and induction of DNA damage by promoting the degradation of TYMS. Our results provide evidence that cinobufagin might be a potential agent for the treatment of cancers such as hepatocellular carcinoma. It can also promote the scientific development of Chansu, and has great significance for enriching the application of TCM in the development of new anti-tumor drugs. Highlights: Cinobufagin promotes proteasome-dependent degradation of TYMS in HCC cells. Cinobufagin inhibits cell growth and induces DNA damage via suppression of TYMS. Cinobufagin in combination with 5-FU exhibits antagonism or synergism effects.